(untitled) (Communications in Mathematical Research, 2021)
Properties of the p-measures of asymmetry and the corresponding affine equivariant p-critical points, defined recently by the second author, for convex bodies are discussed in this article. In particular, the continuity of p-critical points with respect to p on (1, +∞) is confirmed, and the connections between general p-critical points and the Minkowski-critical points (∞-critical points) are investigated. The behavior of p-critical points of convex bodies approximating a convex bodies is studied as well.